2010
DOI: 10.1614/ws-09-107.1
|View full text |Cite
|
Sign up to set email alerts
|

Application Placement and Relative Humidity Affects Smooth Crabgrass and Tall Fescue Response to Mesotrione

Abstract: Much research has been conducted on mesotrione activity on crops and weeds, but information is lacking in regards to the relative contribution of soil and foliar absorption of mesotrione. Three experiments conducted at Virginia Tech's Glade Road Research Facility in Blacksburg, VA, evaluated the effects of 50 and 90% relative humidity (RH) on the activity of mesotrione applied to foliage, soil, and soil plus foliage. Tall fescue injury ranged from 0 to 21% and was significant in 6 of 20 comparisons. Three of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 21 publications
(26 reference statements)
3
27
0
Order By: Relevance
“…Johnson and Young (2002) reported that mesotrione was more effective at low temperature and high relative humidity, with foliar application on large crabgrass. Increased relative humidity also was reported to increase smooth crabgrass (Digitaria ischaemum) and tall fescue (Schedonorus phoenix) control by mesotrione application (Goddard et al, 2010). Therefore, more research is needed to explain the different raking effects from 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…Johnson and Young (2002) reported that mesotrione was more effective at low temperature and high relative humidity, with foliar application on large crabgrass. Increased relative humidity also was reported to increase smooth crabgrass (Digitaria ischaemum) and tall fescue (Schedonorus phoenix) control by mesotrione application (Goddard et al, 2010). Therefore, more research is needed to explain the different raking effects from 2 years.…”
Section: Resultsmentioning
confidence: 99%
“…Several triketone herbicides have been shown to control annual grasses (Johnson and Young, 2002; Bollman et al, 2008; Goddard et al, 2010) but are highly injurious to bermudagrass (Brosnan and Breeden, 2013). The amount of bermudagrass injury caused by triketone herbicides depends on the specific herbicide, application rate, and application frequency (Kopsell et al, 2010; Brosnan et al, 2011; Elmore et al, 2011a, 2011b).…”
mentioning
confidence: 99%
“…Reductions in F v /F m occur as soon as 6 h after herbicide treatment, long before the appearance of visual symptoms (Barbagallo et al, 2003). As a result, multiple researchers have used F v /F m assessments to supplement visual ratings of mesotrione activity in field and greenhouse studies (Goddard et al, 2010; McCurdy et al, 2008, 2009; McElroy and Walker, 2009). However, direct relationships between F v /F m and carotenoid pigment concentrations following HPPD‐inhibiting herbicide treatment to turfgrass have not been reported.…”
mentioning
confidence: 99%